The platelet transcriptome and proteome in Alzheimer’s disease and aging: an exploratory cross-sectional study - de Sousa, Diana M. Bessa; Poupardin, Rodolphe; Villeda, Saul A.; Schroer, Adam B.; Fröhlich, Thomas; Frey, Vanessa; Staffen, Wolfgang; Mrowetz, Heike; Altendorfer, Barbara; Unger, Michael S.; Iglseder, Bernhard; Paulweber, Bernhard; et al. (Frontiers in Molecular Biosciences, 2023)
Alzheimer’s disease (AD) and aging are associated with platelet hyperactivity. However, the mechanisms underlying abnormal platelet function in AD and aging are yet poorly understood. To explore the molecular profile of AD and aged platelets, we investigated platelet activation (i.e., CD62P expression), proteome and transcriptome in AD patients, non-demented elderly, and young individuals as controls. AD, aged and young individuals showed similar levels of platelet activation based on CD62P expression. However, AD and aged individuals had a proteomic signature suggestive of increased platelet activation compared with young controls. Transcriptomic profiling suggested the dysregulation proteolytic machinery involved in the regulation of platelet function, particularly in the ubiquitin-proteasome system in AD and autophagy in aging. The functional implication of these transcriptomic alterations remains unclear and requires further investigations.